Choosing the tool for osteoporosis risk prediction. Issue 5 (September 2015) - Cormier, Catherine; Koumakis, Eugenie; Souberbielle, Jean-Claude
Abstract : Purpose of review: Predicting fracture risk is a major challenge because it allows the prevention of major osteoporotic fracture in high-risk populations. With the aging of the population, this matter will become of even greater importance. In recent years, novel clinical, biochemical, and imaging tools have been developed to improve the assessment of fracture risk. Recent findings: The present review summarizes novel clinical strategies, Dual energy X-ray absorptiometry (DXA)-derived tools, imaging techniques, and biochemical markers that have been developed recently to improve fracture risk prediction. Summary: DXA and clinical fracture risk prediction tools are preferential markers of fracture risk. Clinical fracture risk alone might be used if DXA facilities are unavailable. The fracture risk assessment tool may be used in osteoporosis consultation in many countries. Other tools may be used soon after more studies are performed, particularly trabecular bone score, quantitative ultrasound, bone turnover markers. Specific factors for example falls, hip axis length, vertebral fracture assessment could be used in individual patients. This may significantly improve the clinical decision-making.